2019
DOI: 10.1126/sciadv.aav7199
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared upconversion–activated CRISPR-Cas9 system: A remote-controlled gene editing platform

Abstract: As an RNA-guided nuclease, CRISPR-Cas9 offers facile and promising solutions to mediate genome modification with respect to versatility and high precision. However, spatiotemporal manipulation of CRISPR-Cas9 delivery remains a daunting challenge for robust effectuation of gene editing both in vitro and in vivo. Here, we designed a near-infrared (NIR) light–responsive nanocarrier of CRISPR-Cas9 for cancer therapeutics based on upconversion nanoparticles (UCNPs). The UCNPs served as “nanotransducers” that can co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(134 citation statements)
references
References 45 publications
1
132
0
1
Order By: Relevance
“…For example, after administration nanocarriers can be activated by an external stimuli, such as light. [161][162][163] Ren et al developed nanocarriers that sequentially release miRNA in response to pH and doxorubicin in response to near-infrared-radiation (NIR). [164] They loaded doxorubicin inside a hollow gold nanoparticle, and then attached polyamidoamine (PAMAM) around the gold nanoparticle.…”
Section: Using Systems Biology To Optimize Payload Selection and Sequmentioning
confidence: 99%
“…For example, after administration nanocarriers can be activated by an external stimuli, such as light. [161][162][163] Ren et al developed nanocarriers that sequentially release miRNA in response to pH and doxorubicin in response to near-infrared-radiation (NIR). [164] They loaded doxorubicin inside a hollow gold nanoparticle, and then attached polyamidoamine (PAMAM) around the gold nanoparticle.…”
Section: Using Systems Biology To Optimize Payload Selection and Sequmentioning
confidence: 99%
“…Pan et al applied this approach in CRISPR gene editing for cancer therapeutics. [193] They coated the UCN surface with ONB-caged Cas9-sgRNA, a single guide RNA that targets a tumor gene (polo-like kinase-1). NIR irradiation led to desired gene editing as verified by inhibition of tumor growth in vivo.…”
Section: Nucleotidesmentioning
confidence: 99%
“…NIR irradiation led to desired gene editing as verified by inhibition of tumor growth in vivo. [193] Another example for gene release involved UCN loaded with an ONB-caged morpholino oligonucleotide on the surface. [194] This system enabled NIR-triggered gene escape in endosomes by which gene knockdown occurred more effectively in a melanoma model.…”
Section: Nucleotidesmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these issues, far-red light-mediated CRISPR-dCas9 device, which is built based on the bacterial photoactivatable cyclic diguanylate monophosphate (c-di-GMP) synthase BphS and the c-di-GMP-responsive hybrid transactivator, has been recently developed for the targeted epigenetic modulation both in vitro and in vivo 34 . Most recently, near-infrared upconversion-activated CRISPR-Cas9 nanoparticle system have been proposed for the optical control of therapeutic gene editing towards cancer treatment 35 . While above two studies revealed the infrared light is critical for the regulation of genome editing and epigenome editing in vivo, the precise CRISPR/Cas9 genome editing in a programmable, reversible manner has not been demonstrated yet, not to mention those for in vivo applications.…”
Section: Introductionmentioning
confidence: 99%